2008
DOI: 10.1007/s12221-008-0114-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of various blend ratios of prepared masterbatch containing Ag/TiO2 nanocomposite on the properties of bioactive continuous filament yarns

Abstract: In this research, possibility of producing and processing antibacterial organic/inorganic nanocomposite polypropylene filament yarns for permanent antimicrobial efficiency has been investigated. First PP powder and inorganic nanocomposite filler were mixed in a twin screw extruder and modified masterbatch was produced. Continuous filament yarn was made by a pilot plant melt spinning machine from the blend of PP granule and various blending contents of the prepared masterbatch. Pure PP and all other combined sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…The rutile is thermodynamically more stable than the anatase and brookite. At high temperature, the anatase and brookite are Increasing the available nano-silver particles via surface coating of nanosilver on titanium dioxide [101,102].…”
Section: Tio 2 Nano-particlesmentioning
confidence: 99%
“…The rutile is thermodynamically more stable than the anatase and brookite. At high temperature, the anatase and brookite are Increasing the available nano-silver particles via surface coating of nanosilver on titanium dioxide [101,102].…”
Section: Tio 2 Nano-particlesmentioning
confidence: 99%
“…However, NPs can be incorporated into polymer matrix leading to a new generation of antimicrobial agents with potential use in areas such as medicine, food packaging, and textile fibers. In this context, Dastjerdi et al [9] obtained filament yarns based on polypropylene (PP)/(nTiO 2 /Ag), in order to evaluate the antimicrobial activity by varying the concentration from 0.2 to 1 wt-% of NPs. These authors found that 0.75 wt-% of NPs is the optimal bactericidal content and increasing the content 2 Journal of Nanomaterials up to 1 wt-% of NPs they observed a significant reduction in the antimicrobial activity because of the NPs agglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…For treating textiles, there are several different forms of nanosilver in use, e.g., metallic silver nanoparticles (Ag NP) , silver chloride particles (AgCl NP) (Tomšič et al 2009) and silver-titanium dioxide composite nanoparticles (Ag/TiO 2 NC) Yuranova et al 2006). In the case of antimicrobial efficiency, the surface coating of nanosilver on titanium dioxide maximizes the number of particles per unit area in comparison with the use of an equal mass fraction of pure silver (Dastjerdi et al 2008;Rimai et al 2000). TiO 2 nanoparticles activated by UV radiation have excellent photoactivity, high stability and antimicrobial properties, furthermore the incorporation of TiO 2 into textiles increases the UV protection factor of textiles (Montazer and Seifollahzadeh 2011;Sundaresan et al 2012;Ugur et al 2011).…”
Section: Introductionmentioning
confidence: 99%